The Possible Unemployment Cost of Average Inflation Below a Credible Target. A Replication Study of Svensson (American Economic Journal: Macroeconomics, 2015) - Ramy Oraby (Journal of Comments and Replications in Economics (JCRE), 2022)
This paper replicates the main analysis of Svensson (2015) with some expansion to the original analysis, mainly for the United States. Overall, the replication exercise successfully confirms the conclusions of Svensson (2015). In both Sweden and the United States, empirical evidence sup- ports the existence of a non-vertical long run Phillips curve. The slope of the long run Phillips curve recorded -0.75 in Sweden and -0.23 in the United States. While the average inflation rate in the United States was very close to its targeted level, the average inflation rate in Sweden was 0.6 per- centage points below its targeted level over the sample period. The deviation of inflation rate from its targeted level in Sweden resulted in an unemployment cost equivalent to 0.8 percentage points over the sample period where the average unemployment rate recorded 7.4 percent compared with an estimated 6.6 percent had the average inflation rate been at its targeted level.
https://doi.org/10.15456/j1.2021152.143135
Keywords: D84; E24; E31; E52; E58; 330; Monetary Policy; Central Banks; Phillips Curve; Inflation; Expectations; Unemployment; Replication Study